(3ehShYI gPG GdQLd ef eUQs - (3deYj GdeWjYj(B.s ((3eOjfI fUQ (B:s (3OGQ GdTQhb(B,s, 1997)
(3ehShYI JJVef eYdheGJ Yf (B90 (3QLd ef eUQ GKGQhGGdMjGI GdSjGSjI h GdGLJeGYjI h GdKbGajI h GdacQjI(B.( (3GdeLdO GdGhd (B) (3GeG GdKGfi jVe fSGA h QLGd ef eUQ GKGQhG GdMjGI GdacQjI h GdSjGSjI h GdGLJeGYjI(B.s
(3JJchf GdehShYI ef eLdOjf GdGhd gh gPG GdQLd ef eUQ h GdKGfi gh fSGA h QLGd ef eUQ(B.s
(3ehShYI JJVef eYdheGJ Yf QLGd GKGQhG GdMjGI GdSjGSjI h GdGLJeGYjI h GdKKbGajI(B.s
Keywords: (3QLGd (B- (3eUQ (B.s -- (3fSGA (B- (3eUQ(B.s